Indonesia dalam Pusaran Politik Energi Global - Angga Nurdin Rachmat (Indonesian Perspective, 2018)
Energy emerges as a strategic issue as industrial countries begin to strive to increase their economic growth. This condition is related to the need for source, distribution and price of guaranteed energy sources. The achievement of these conditions will not be easy because the must compete each other for energy accsess. However, for developing countries with considerable energy reserves this condition leads them in two situations where the first will be a bargaining power that leads to the achievement of national interests and on the other hand will be a curse that makes them an object of exploitation of advanced industrial countries. Referring to these conditions Indonesia is a country with a lot of resources. Therefore, this paper describes the dynamics of global energy politics and how Indonesia should take advantage of the opportunity of the dynamics of global energy politics.Keywords: global energy politics, industrial countries, Indonesia